ANALISIS IMPLEMENTASI CYBER SECURITY PADA SISTEM INFORMASI INVENTORY DI PERUSAHAAN DAGANG - Sumaryanto Sumaryanto; Purwati Purwati; Setiyo Prihatmoko (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
Digital transformation in the business world has driven trading companies to utilize inventory information systems to improve operational efficiency and stock data accuracy. However, along with the increasing dependence on digital systems, serious challenges related to data and system security have emerged, especially in facing cyber threats. This study aims to analyze the implementation of cybersecurity in the inventory information system of a trading company, in order to evaluate the extent of protection applied to data and infrastructure. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation studies at a trading company. The results show that the implementation of cybersecurity in the inventory information system is still not optimal, characterized by weak access controls, the absence of an intrusion detection system, and a lack of documented security policies. This study provides recommendations such as the implementation of role-based access control, strengthening data encryption, as well as the development of security policies and regular training for system users. With improved cybersecurity implementation, companies are expected to minimize the risk of system disruptions and protect critical data from both external and internal threats.